Prevalence of food insecurity among students attending four Historically Black Colleges and Universities. Issue 1 (2nd January 2023) - Duke, Naomi N.; Campbell, Santiba D.; Sauls, Derrick L.; Stout, Robyn; Story, Mary T.; Austin, Tomia; Bosworth, Hayden B.; Skinner, Asheley C.; Vilme, Helene
Abstract: Objective: This study examined the prevalence of food insecurity (FI) among students attending Historically Black Colleges and Universities (HBCUs) in the Southeastern United States. Participants: Students attending four HBCUs ( N  = 351) completed an anonymous Web-based survey. Methods: Food insecurity was assessed using the 2-item Hunger Vital Sign Tool. Summary statistics were used to quantify FI experiences. Logistic regression was conducted to determine if student demographic characteristics were significantly associated with FI outcomes. Results: Nearly 3 in 4 students (72.9%) reported some level of FI in the past year. Students representing all levels of postsecondary education reported FI. Meal plan participation did not prevent FI. Conclusions: Students attending HBCUs experience FI at levels that exceed estimates reported among students attending predominantly White institutions. More work is needed to understand the lived experience of food-insecure HBCU students as a means to ensure institution-level food policies support student academic success and wellbeing.